MORPHOLOGICAL AND ANATOMICAL CHARACTERS FEATURES OF THREE MEDICINAL SCANDIX SPECIES (APIACEAE) FROM TURKEY - Demirpolat, Azize; Dogan, Gulden; Bagci, Eyup (Pakistan Botanical Soc, 2019)
Genus Scandix is represented by 9 taxa in Turkey. They are the medicinal and aromatic plants because of their utility for various medicinal purposes. In this study, morphological, morphometrical and anatomical features of the some Scandix species (Scandix stellata, Scandix iberica and Scandix aucheri) from Turkey were investigated to compare and determine the taxonomic importance of these characters in the genus. The description, synonyms, Turkish names, flowering times, habitat characteristics of each taxon were presented. Anatomical investigations, including cross sections taken from stems, root and fruit of each species, were examined using light microscope. For the first time, anatomical as well as morphological studies of S. stellata and S. aucheri were conducted. The anatomical features of stem, root and fruit structures of these species were quite similar.
Keywords: Anatomy; Apiaceae; Morphology; Scandix; Turkey